Porn Empowerment: Negotiating Sex Work and Third Wave Feminism - Martin, Nina K. (Atlantis)

(untitled) (Mount Saint Vincent University, 2007)
This article examines the ubiquitousness of sexy female bodies in popular culture, and assesses what impact the mainstreaming of porn and sex work has on feminism and female empowerment, exploring the ironic tension between the feminist struggle to freely express oneself sexually through sex work and its co-optation and selling by pop culture to young women as a sexy, empowered lifestyle choice.